Decision Support System for Suitability of Horticultural Agricultural Plant Types with Land Conditions Using Interpolation Profile Matching - Petrus Wolo; Sri Mulyana; Retantyo Wardoyo (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2023)
Horticultural crops are the most produced by farmers in the Napugera Village area because they are more profitable to cultivate because they are short in life and from an economic point of view they are obtained faster. However, has often experienced obstacles, one of which is determining the suitability of agricultural land for horticultural crops. Determining the selection of horticultural crops for the types of red onion, red red chili, and tomato crops on a field based on land conditions is very necessary for farmers in the Napugera Village area as a support for decision-making. There are 8 criteria assessed including temperature, rainfall, air humidity, soil type, soil texture, soil ph, land slope and topography. In this study, a profile-matching interpolation method was developed for a decision-making system that can be used as a tool in providing decisions on plants that are suitable for planting in a field easily, quickly, and accurately. The profile-matching interpolation method is one of the methods of scoring data. The results showed that the type of onion horticultural crop with a final value of 3,764 is suitable for cultivation in the Napugera Village area.